PERDAGANGAN SKINCARE “KW” DI PASAR TRADISIONAL PONTIANAK PERSPEKTIF KOMISI FATWA MAJELIS ULAMA INDONESIA NOMOR 1 TAHUN 2003 TENTANG HAK CIPTA - Noriraya Noriraya; Sukardi Sukardi; Abu Bakar (Al-Aqad, 2022)
This research is prompted by the widespread of sale particularly skincare in the counterfeiting of goods or "KW". One of the historic marketplaces in Pontianak that sells a variety of skincare items is the Pasar Tengah, which is located on Jalan Kapten Marsan in Pontianak Kota. Observations led researchers to conclude that multiple Street Vendor stands in the area sold KW skincare items. This study's objective is to determine the KW skincare trading system in the Pontianak Central Market and the legal position of KW skincare trading in the Pontianak Central Market from the perspective of the Fatwa Commission of the Indonesian Ulema Council Number 1 of 2003 regarding copyright. Utilizing a sociological-empirical methodology, the research method employed is qualitative. Skincare sellers and purchasers in Pasar Tengah are the primary data sources. In the meantime, secondary data was collected from a variety of sources, including journals and Fatwas of the Fatwa Commission of the Indonesian Ulema Council, which in this instance was Fatwa Number 1 of 2003 about Copyright. The findings revealed that: 1. The sales system employed by sellers who refer to KW items with other designations, such as "Local Goods," is indicative of the dishonesty value of the trading method used for KW skincare marketed in Pontianak Central Market. The practice is founded on the importance of consumer pleasure with the immediate results of the skincare product. 2). The legal position of trade KW skincare has become void and illegitimate because it violates the Fatwa Commission of the Indonesian Ulema Council Number 1 of 2003 about Copyright.